Testosterone related to age and life-history stages in male baboons and geladas - Beehner, Jacinta C.; Gesquiere, Laurence; Seyfarth, Robert M.; Cheney, Dorothy L.; Alberts, Susan C.; Altmann, Jeanne (Hormones and behavior, 2009)
Despite significant advances in our knowledge of how testosterone mediates life-history trade-offs, this research has primarily focused on seasonal taxa. We know comparatively little about the relationship between testosterone and life-history stages for non-seasonally breeding species. Here we examine testosterone profiles across the life span of males from three non-seasonally breeding primates: yellow baboons (Papio cynocephalus or P. hamadryas cynocephalus), chacma baboons (Papio ursinus or P. h. ursinus), and geladas (Theropithecus gelada). First, we predict that testosterone profiles will track the reproductive profiles of each taxon across their respective breeding years. Second, we evaluate age-related changes in testosterone to determine whether several life-history transitions are associated with these changes. Subjects include males (>2.5 years) from wild populations of each taxon from whom we had fecal samples for hormone determination. Although testosterone profiles across taxa were broadly similar, considerable variability was found in the timing of two major changes: (1) the attainment of adult levels of testosterone and (2) the decline in testosterone after the period of maximum production. Attainment of adult testosterone levels was delayed by 1 year in chacmas compared with yellows and geladas. With respect to the decline in testosterone, geladas and chacmas exhibited a significant drop after 3 years of maximum production, while yellows declined so gradually that no significant annual drop was ever detected. For both yellows and chacmas, increases in testosterone production preceded elevations in social dominance rank. We discuss these differences in the context of ecological and behavioral differences exhibited by these taxa.